A Bibliometric Study of Worldwide Trends in Teaching Fiction in English Literature - Rizka Safriyani; Muhammad Farid Ubaidillah; Siti Uswatun Khasanah (Loquen, 2026)
This study employs bibliometric analysis to map international trends in teaching fiction in English literature classrooms, including trends in publication, major scholars, and emerging themes. According to the Scopus database statistics, research papers published from 2010 to 2024 were queried with the terms "Teaching Fiction," "English Literature," and "Learning Approaches." The findings reveal a strong local publication focus and a lack of robust international collaboration, with the United States, the United Kingdom, Australia, Russia, and China emerging as leading players. Scholars such as Ivey Gay and Astradur Esteinsson have worked on multimodal teaching approaches and digital storytelling, respectively. Dominant thematic trends, including "Education," "Learning," and "Curriculum," reveal an increasing emphasis on creativity, critical thinking, and digital content in fiction pedagogy. These findings provide a valuable stepping stone to research in innovative methodologies and pedagogical practice within teaching fiction